Soft Information Adjustor for Four-Head/Two-Track (4H/2T) Bit-Patterned Magnetic Recording - Rueangnetr, Natthakan; Warisarn, Chanon; Koonkarnkhai, Santi; Kovintavewat, Piya (My University, 2022)
To mitigate the two-dimensional (2D) interference and track misregistration (TMR) effect, we have previously proposed a TMR correction method combined with the soft-information adjustor (SIA) technique. In practice, the SIA technique uses the advantage of a 2D soft-output Viterbi algorithm (SOVA) detector to improve the reliability of the log-likelihood ratio (LLR) before deciding the estimated user bits. To further improve its performance, this paper proposes a novel SIA scheme by exploiting the advantage of the 2D SOYA detector to improve the LLR reliability of the estimated data bits for the considered upper- and lower-track in four-head/two-track (4H/2T) bit-patterned magnetic recording system. The simulation results indicate that the proposed system can deliver a better BER performance over the conventional SIA system, in particular when the system experiences media noise.
Keywords: bit-patterned magnetic recording (BPMR); four-head/two-track (4H2T); soft-output Viterbi algorithm (SOVA); track misregistration (TMR)